2014
DOI: 10.1111/papr.12231
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Quality of Life after 3 months of Usual Care in a Large Sample of Patients with Noncancer Pain: The “QOOL: Quality of Life and Pain” Study

Abstract: Large-scale observational studies can provide useful information on changes in health outcomes over time. The aim of this study was to investigate the effect of 3 months of usual care on quality of life (QOL) and pain outcomes in noncancer chronic pain patients managed by pain specialists and to examine factors associated with changes in QOL. This was assessed using the EQ-5D and pain outcomes using the Brief Pain Inventory (BPI). Changes in QOL and pain were studied for the overall sample and in subgroups def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(43 reference statements)
0
3
0
1
Order By: Relevance
“…In terms of the factors associated with change in QoL in all types of cancer, the most relevant were baseline performance status, change on the BPI severity and interference sub-scales, EQ-5D Index score at baseline, and presence of anxiety/depression at both visits. An earlier study demonstrated the relationship between improvements in pain as measured by the BPI and improvements in QoL [ 22 ], though that was not performed in cancer patients. The effect of changes in pain on QoL scores is strong, with the regression analysis suggesting that an approximately two point change on either the BPI pain severity or pain interference sub-scales would lead to a change on the EQ-Index which would be close to its minimal important difference (MID), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the factors associated with change in QoL in all types of cancer, the most relevant were baseline performance status, change on the BPI severity and interference sub-scales, EQ-5D Index score at baseline, and presence of anxiety/depression at both visits. An earlier study demonstrated the relationship between improvements in pain as measured by the BPI and improvements in QoL [ 22 ], though that was not performed in cancer patients. The effect of changes in pain on QoL scores is strong, with the regression analysis suggesting that an approximately two point change on either the BPI pain severity or pain interference sub-scales would lead to a change on the EQ-Index which would be close to its minimal important difference (MID), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…En todas las dimensiones del EQ-5D se observó una reducción considerable en la proporción de pacientes que reportaban problemas moderados a severos, especialmente, en las dimensiones depresión/ansiedad, dolor/malestar y actividades habituales. Adicionalmente, se encontraron mejoras significativas en la severidad e interferencia del dolor media de la muestra, siendo mayores en aquellos pacientes con un dolor basal más severo (Velázquez Rivera et al, 2015).…”
Section: Impacto Del Tratamiento Para El Dolor En La Calidad De Vida ...unclassified
“…Observational studies have shown patients with chronic pain to report moderate impairment (5.6/10 to 6.6/10) on the BPI-Interference Scale. 19,20 The Hamilton Anxiety and Depression Scale (HADS) is a 14-item questionnaire consisting of anxiety (HADS-A) and depression (HADS-D) subscales that was used to measure psychological distress. 21 Each subscale contains 7 items with score ranges from 0 to 21, in which 0-7 is no distress, 8-10 is mild distress, 11-14 is moderate distress, and 15-21 is severe distress.…”
Section: Psychometric Measuresmentioning
confidence: 99%